A Large-Bandgap Conjugated Polymer for Versatile Photovoltaic Applications with High Performance - Zhang, Maojie (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.